How the 2025 NIH grant terminations varied by researchers’ demographic groups - Diego F. M. Oliveira; Qian Huang; Teresa K. Woodruff; Brian Uzzi (Proceedings of the National Academy of Sciences, 2026)
In early 2025, the NIH unexpectedly terminated 2,291 active research grants, withdrawing $2.45 billion and disrupting thousands of projects. While the economic magnitude of these cuts is known, less is understood about how they differed across researchers’ demographic groups. Using an original dataset of publicly available records, we documented how cancelations varied by gender and career stage. Although cuts occurred across all regions and institution types, statistical patterns show that early-career investigators—assistant professors, postdoctoral scholars, trainees, and graduate students—were disproportionately affected, as were women. Women’s projects were smaller on average, had a larger share of unspent funds at cancelation, and were more concentrated in training and transition awards. Although available data cannot determine downstream causal effects, NIH economic multipliers suggest a potentially large unrealized loss to the US research enterprise. These patterns highlight the vulnerability of early-career researchers and women to abrupt funding instability and underscore the need for sustained investment to protect the future scientific workforce.